2003
DOI: 10.1136/bmj.326.7379.13
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of breast feeding in term neonates: randomised controlled trial

Abstract: Objectives To investigate whether breast feeding is effective for pain relief during venepuncture in term neonates and compare any effect with that of oral glucose combined with a pacifier. Design Randomised controlled trial. Participants 180 term newborn infants undergoing venepuncture; 45 in each group. Interventions During venepuncture infants were either breast fed (group 1), held in their mother's arms without breast feeding (group 2), given 1 ml of sterile water as placebo (group 3), or given 1 ml of 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
26

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(152 citation statements)
references
References 15 publications
(13 reference statements)
5
115
0
26
Order By: Relevance
“…[52][53][54][55][56][57] Kangaroo care 58,59 and breastfeeding [60][61][62][63][64] were more or equally effective, compared with sucrose alone, in most studies, with few exceptions. [65][66][67] Sucrose or glucose was equal to or more effective than eutectic mixture of topical anesthetics during heel lances, 68 finger pricks, 69 …”
Section: Additional Interventions Studiedmentioning
confidence: 99%
“…[52][53][54][55][56][57] Kangaroo care 58,59 and breastfeeding [60][61][62][63][64] were more or equally effective, compared with sucrose alone, in most studies, with few exceptions. [65][66][67] Sucrose or glucose was equal to or more effective than eutectic mixture of topical anesthetics during heel lances, 68 finger pricks, 69 …”
Section: Additional Interventions Studiedmentioning
confidence: 99%
“…These include use of oral sucrose/glucose, [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] breastfeeding, 77 nonnutritive sucking, 49,78 "kangaroo care" (skin-to-skin contact), 55,58 facilitated tuck (holding the arms and legs in a flexed position), 79 swaddling, 80 and developmental care, which includes limiting environmental stimuli, lateral positioning, the use of supportive bedding, and attention to behavioral clues. 61 These measures have been shown to be useful in preterm and term neonates in reducing pain from a heel stick, 68,[70][71][72][73]79,80 venipuncture, 62,64,65,67,74,77,81 and subcutaneous injections 81 and are generally more effective when used in combination than when used alone. 63,65,68,69,80,82 Concentrated oral sucrose has been widely studied.…”
Section: Nonpharmacologic Pain Prevention For Minor Proceduresmentioning
confidence: 99%
“…A number of studies have advocated the analgesic effect of breast feeding during painful procedures (Carbajal et al, 2003;Gray et al, 2002). Carbajal et al (2003) studied 180 babies undergoing venepuncture and found that breastfeeding during the procedure significantly reduced the infant's apparent pain.…”
Section: Discussionmentioning
confidence: 99%